Home policy towards religion and religious interaction in the foreign states (Journal of Philosophy Culture and Political Science, 2019)
This article analyzes the public policies of foreign countries in the sphere of religion and religious relations. And also considers modern religious situation in post-Soviet states, the impact of non-traditional religions in the public consciousness and the current state of religious associations. Keywords: public policy, religious relationships, religious associations and confessions.